2019
DOI: 10.1002/jmor.20962
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of spider thread anchorages

Abstract: Spiders attach silken threads to substrates by means of glue‐coated nanofibers (piriform silk), spun into disc‐like structures. The organization and ultrastructure of this nano‐composite silk are largely unknown, despite their implications for the biomechanical function and material properties of thread anchorages. In this work, the ultrastructure of silken attachment discs was studied in representatives of four spider families with Transmission Electron Microscopy to facilitate a mechanistic understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…Based on the observation of Wirth et al (2019) that in C. salei the glue fraction of piriform silk is much smaller (i.e., mean thickness of ∼20 nm) than the fiber fraction (thickness of ∼0.5-1.5 µm), we neglected the presence of the glue (third phase) in the calculation of the volume. We assume that the density of the piriform silk is similar to that of major ampullate silk (ρ p ∼ ρ silk ∼ 1.3 g cm 3 = ρ).…”
Section: Evaluation Of the Spacing Among Fibrilsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the observation of Wirth et al (2019) that in C. salei the glue fraction of piriform silk is much smaller (i.e., mean thickness of ∼20 nm) than the fiber fraction (thickness of ∼0.5-1.5 µm), we neglected the presence of the glue (third phase) in the calculation of the volume. We assume that the density of the piriform silk is similar to that of major ampullate silk (ρ p ∼ ρ silk ∼ 1.3 g cm 3 = ρ).…”
Section: Evaluation Of the Spacing Among Fibrilsmentioning
confidence: 99%
“…The sectioning of attachment discs revealed that the relative proportion of the cement-like glue and the fiber content of the attachment discs differs between spiders of different ecology and evolutionary history; and that the piriform fibers and the dragline are not in contact with the substrate (Denny, 1976;Wirth et al, 2019). Accordingly, the fibers are not directly involved in the attachment disc's adhesion, yet they may modulate the mechanical properties of the surrounding glue layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Wirth et al. ). The openings of the numerous small piriform glands are grouped on the tip of the second pair of spinnerets (the “anterior lateral spinnerets”) around one or few openings of the large “major ampullate” glands, which produce the silk thread (“dragline”) used to build the web scaffold (Eberhard ).…”
mentioning
confidence: 98%